Effect of chainring ovality on joint power during cycling at different workloads and cadences - Strutzenberger, G.; Wunsch, T.; Kroell, J.; Dastl, J.; Schwameder, H. (Sports Biomechanics, 2014)
Non-circular chainrings theoretically enhance cycling performance by increasing effective chainring diameter and varying crank velocity, but research has failed to consistently reproduce the benefits in cycling trials. The aim of this study was (1) to investigate the effect of different chainring shapes on sagittal knee joint moment and sagittal lower limb joint powers and (2) to investigate whether alterations are affected by cadence and workload. Fourteen elite cyclists cycled in six conditions (70, 90 and 110 rpm, each at 180 and 300 W), for 2 min each, using three chainrings of different ovalities (1.0-1.215). Kinematic data and pedal forces were collected. For most conditions, only the chainring with the highest ovality (1.215) was characterised by smaller sagittal knee joint moments, smaller relative sagittal knee joint power contribution and larger relative sagittal hip joint power contribution, which suggests a change from maximising efficiency to maximising power production. Effect sizes increased with higher cadences, but not with higher workload. This study has application for athletes, clinicians and sports equipment industry as a non-circular chainring can change joint-specific power generation and decrease knee joint moment, but certain ovality seems to be necessary to provoke this effect.